376PAdoption of molecular testing in breast cancer in a tertiary care center in a developing country. (24th November 2019) - Dash, P K; Koyyala, V P B; Suryavanshi, M; Jajodia, A; Pasricha, S; Goel, V; Bothra, S J; Goyal, S; Batra, U; Doval, D C
Abstract: Background: The clinical application of rapidly developing new molecular tests in breast cancer is debatable and often not affordable for most of the patients from developing countries. We assessed the adoption of molecular testing and their utility in breast cancer patients in the setting of a developing Nation. Methods: We analysed the results of next-generation sequencing (NGS) based BRCA1 and 2 and multi-gene testing, immunohistochemistry based (IHC) based mismatch repair genes (MMR), Programmed cell death ligand 1(PDL1) and Androgen receptor (AR) testing done in breast cancer patients diagnosed from 2015 to 2018. Results: There was an overall increase in the number of molecular tests offered to breast cancer patients in subsequent years. 141 patients opted for BRCA testing out of which 56 (40%) were triple negative (TNBC). 27(19%) out of 141 patients were BRCA mutated and 8(6%) had variants of unknown significance (VUS). Among 15 metastatic breast cancer patients tested for mutations on Multi-gene NGS, 3 had Her2neu amplification. Out of 8 TNBC cases, 5 had TP53 mutation, 1 had exon 14 skipping mutation of MET gene and 1 showed EGFR amplification. None of the five and six breast cancer patients with TNBC tested for MMR and PD-L1 were MMR deficient or positive respectively. Of the 7 TNBC patients tested, 4 were found to have Androgen receptor expression. Conclusions: There is a significant rise in the use of modern molecular techniques in developing nations like India. However, Country Specific guidelines guided by International guidelines and awareness in patients with specific counseling on advantages and disadvantages of these tests may help in the usage of these techniques by most needy patients, breast cancer in particular. Legal entity responsible for the study: Rajiv Gandhi Cancer Institute and Research Centre, New Delhi. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.